Integration of HIV and maternal healthcare in a high HIV-prevalence setting: analysis of client flow data over time in Swaziland. Issue 3 (7th March 2014) - Birdthistle, Isolde J; Mayhew, Susannah H; Kikuvi, Joshua; Zhou, Weiwei; Church, Kathryn; Warren, Charlotte E; Nkambule, Rejoice; Fenty, Justin; ,
Abstract : Objective: Maternal and child health (MCH) care may provide an entry point for HIV services in high HIV-prevalence settings. Our objective was to assess integration of HIV with MCH services in public sector facilities in Swaziland. Design: In 2009, 2010 and 2012, client flow assessments (CFAs) were conducted over 5 days in the MCH units of eight government facilities, purposively selected as intervention or comparison sites. Participants: 8263 MCH visits with female clients were tracked: 3261 in 2009, 2086 in 2010 and 2916 in 2012. Intervention: Activities and resources to strengthen integration of HIV services into postnatal care (PNC), 2009–2010. Main outcome measures: The proportion of all visits in which an HIV/sexually transmitted infection (STI) testing, counselling or treatment was received together with an MCH service; the proportion of all visits in which a client receives HIV counselling. Results: Across facilities, the proportion of visits in which HIV/STI and MCH services were received varied considerably, for example, from 9% to 49% in 2009. HIV/STI services were integrated most frequently with child health (CH), antenatal care (ANC) and family planning (FP)—the most common reasons for women's attendance—and least often with PNC and cervical screening (CS). There was no meaningful difference in integration over time by design group and considerable heterogeneity across facilities. Receipt of integrated services increased in one intervention and two comparison facilities, where HIV counselling also rose, and fell in one intervention and two comparison facilities. Conclusions: Provision of HIV/STI services with MCH care occurred at all facilities, yet relatively few women receive integrated services. Increases in integration were driven by increases in HIV counselling, while sharp declines in some facilities indicate that integration is difficult to sustain. Opportunities for intensifying HIV integration lie with ANC, CH and FP, while HIV-PNC integration will remain limited until more women attend PNC. Trial registration number: Current Controlled Trials NCT01694862 .